Indeks Kesesuaian Wisata Dan Strategi Pengembangan Wisata Pantai Di Kawasan Pantai Munggu, Badung, Bali. - Ni Luh Intan Kartika Sari; I Wayan Restu; I Ketut Wija Negara (Environmental Research Center (PPLH) of Udayana University, 2023)
Research on tourism conformity index (IKW) and beach tourism development strategy was carried out in Munggu Beach, Munggu Village, Mengwi District, Badung. IKW data collection and questionnaire interviews were conducted in January-February 2022 with 3 IKW measurement points. The research aims to find out the value of IKW conditions and development strategies that can be used for management. The methods used are descriptive and quantitative. Primary data is based on observation of beach type parameters, beach width, beach slope, water base material, land closure, availability of clean water, and questionnaire interviews with beach visitors with purposive sampling techniques. Data analysis using IKW measurement results and SWOT analysis. Based on the calculation of IKW at 3 points, namely point I of 1,505, point II of 1,595, and point III of 1,395. The total analysis value of 1? IKW <2.0 belongs to the category of non-conformity. This is due to the weak factors that are owned, so to be developed must be done to improve management. Strategies that can be applied at Munggu Beach are WT (Weakness-Threats) strategy, such as continuing alternative tourism at Munggu Beach, involving the ekternal management of Munggu Beach and adding tourist attractions to Munggu Beach. Keywords: Munggu Beach, IKW, Development Strategi in Munggu Beach